Use of websites or other sources of information for the prevention of chronic non-communicable diseases - Alves Antonio, Alan (2021)
Objective. Describe the frequency of use of websites or digital media for the prevention of chronic non-communicable diseases in the city of Cochabamba, Bolivia. Methods. The study involved 303 persons classified according to sex: 156 women and 147 men; in relation to housing: 279 inhabitants of Cochabamba and 24 from other places and according to the degree of education: 208 with university level, 90 with high school level and 5 with other degrees of education. 63 websites were evaluated that met the requirements of having at least a score of 60 points on the checklist. Results. 227 people used the digital media to obtain information on NCDs, 27 used (public) health posts, 32 used private clinics and the remaining 17 people used traditional doctors, friends, relatives or other means. Of the 63 websites evaluated, all have easy access, 31.7% have a good design and interaction with the user and only 62.4% have satisfactory content. Conclusion. The results show that the majority of the people surveyed (74.9%) use the digital medium as a source of information on NCD prevention but, unfortunately, the websites do not provide complete, safe and reliable information for users.